Laurasian ancestors and "Gondwanan" descendants of Rotoitidae (Hymenoptera: Chalcidoidea): What a review of Late Cretaceous Baeomorpha revealed. (April 2018) - Gumovsky, Alex; Perkovsky, Evgeny; Rasnitsyn, Alexandr
Abstract: BaeomorphinaeYoshimoto, 1975, based on Baeomorpha Brues, 1937, is transferred from TetracampidaeFörster, 1856 and recognized as a junior synonym of RotoitidaeBouček and Noyes, 1987 (Hymenoptera: Chalcidoidea)syn. nov . following ICZN (1999) article 35.5. Inclusions in Taimyr amber (84–100 Ma) assigned to Baeomorpha are reviewed and the following eleven new species, all of Gumovsky, are described: B. avamica sp. nov., B. baikurenis sp. nov., B. bianellus sp. nov., B. caeleps sp. nov., B. gracilis sp. nov., B. ingens sp. nov., B. quattorduo sp. nov., B. quattoruno sp. nov., B. popovi sp. nov ., B. yantardakh sp. nov., and B. zherikhini sp. nov. The recognized species are differentiated in separate keys to females and males and illustrated through microphotography. Two of four previously described Baeomorpha species from Campanian Canadian amber are synonymized: B . distincta Yoshimoto and B . elongata Yoshimoto under B . ovatata Yoshimoto (syn. nov. ). One enigmatic rotoitid inclusion, which differs from Baeomorpha species in the possession of very short stigmal vein, is described as Taimyromorpha pusilla Gumovskygen. et sp. nov . Inclusions containing specimens identified as Baeomorpha and Taimyromorpha are found in amber from Taimyr and Canada that originated from Laurasia, not Gondwana. Two Realms are newly proposed to recognize different Cretaceous faunal elements, a more northern Baeomorpha Realm that is characterized by a temperate or warm temperate climate and very abundant aphid fossils, and the Isoptera Realm, an opposing southward territory with a warmer climate and common termite but rare aphid fossils. The newly described fossils indicate the southern hemisphere distribution of extant Rotoitidae is relictual with the pattern observed being formed at least in part by extinction events, though distributions of the only two extant rotoitid genera, Rotoita Bouček and Noyes, 1987 (New Zealand) and Chiloe Gibson and Huber, 2000 (small area in the southern Chile) may have been more extensive in the past. Both of known regions of extant Rotoitidae have highly suppressed ant faunas, which may suggest that their survival there depended on low biocenotic pressure by ants, perhaps as low as is hypothesized for the Late Cretaceous. The Canadian amber genera Distylopus Yoshimoto, 1975 (Distylopinae) and Bouceklytus Yoshimoto, 1975 (Bouceklytinae) are excluded from Tetracampidae and regarded as Chalcidoidea incertae sedis . Graphical abstract: Highlights: The extinct genus Baeomorpha is recognized as member of Rotoitidae, not Tetracampidae. Extant austral rotoitid distribution is possibly a remnant of past world-wide distribution. Proposed is occurrence of two Cretaceous faunal realms, Baeomorpha and Isoptera.